Model for Community Environmental Health Literacy in Peatlands: Research & Development Study - Dessyka Febria, Zulfan Saam, Nofrizal, Agrina (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Environmental health literacy as a combination of the concepts of environmental literacy and health literacy to develop the skills and competencies needed to understand, evaluate, and seek and use environmental health information, reduce health risks, improve quality of life and protect the environment. The development of a model of environmental health literacy in communities on peatlands using research and development methods. Kcomponents of the environmental health literacy modelin communities on peatlands: (1) competencies in environmental health, (2) knowledge about environmental health, especially peatlands and environmentally based diseases, (3) social consciousness and responsible behavior for environmental health, (4) mapping for social behavior environmental health, (5) preventive care action on health and the environment and (6) the context of environmental health literacy includes health and environmental issues that are related to physical, personal, social, economic, cultural, religious, educational, political and environmental conditions as well as aims to protect the environment and improve the quality of life of people on peatlands.